Determinants of SME Exporting: Insights and Implications. (February 2016) - Pickernell, David; Jones, Paul; Thompson, Piers; Packham, Gary
This study offers insights into determinants of SME exporting according to the characteristics of exporting firms and their resources, thus contributing to a limited literature. The dataset comprised 4, 838 respondents from a survey of the UK Federation of Small Businesses. The dependent variable used was two-category ('do not export' and 'export'), allowing a binary logistic multiple regression approach to be used, with separate binomial (logit) regression equations generated for the complete sample and then for different firm age groupings, allowing relationships between exporting and each individual independent variable to be determined whilst holding all other independent variables in the equation constant. The results show that determinants of SME exporting include industry sector, age and the characteristics of the SME owner-manager, along with the firms' available resources, including the human capital of the owner-manager, use of technology and intellectual property. While an innovation focus was consistently found to be positively linked to exporting, a growth focus was not. These results inform both practice and policy, as the exporting activity of SMEs remains closely linked to economic development policy.